Analysis of Marketing Efficiency F Salak Pondoh Commodities (Salacca Edulis Reinw) for Sale in Traditional Markets in Bogor City - Himmatul Miftah; Elis Marfu'ah; Syaima Lailatul Mubarokah; Arti Yoesdiarti (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze marketing channels, marketing channel efficiency values, marketing margins, and market share of salak pondoh sold in traditional markets in Bogor City. Methods of data collection using primary data and secondary data. The sampling technique of farmers was carried out by purposive sampling and snowball sampling of 31 people. The descriptive analysis method for marketing channel analysis and quantitative analysis is to calculate the value of marketing efficiency, marketing margin, and farmer's share. The results showed that one marketing channel for salak pondoh was not efficient because the channel was too long and involved four marketers.